PENGARUH TEKNIK NAPAS DALAM TERHADAP PERUBAHAN NILAI SATURASI OKSIGEN DAN FREKUENSI NAPAS PASIEN ASMA BRONKHIAL DI INSTALASI GAWAT DARURAT RSUD EMBUNG FATIMAH KOTA BATAM TAHUN 2022 - Octaviani, Yoshinta; Roza, Nelli; Febrina, Trisya Yona (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2023)
Asthma is a disease that occurs in bronchi that do not have a framework of cartilage rings so that there is a sudden narrowing. Based on the Global Initiative for Asthma, in 2021 asthma sufferers worldwide are estimated to be more than 260 million people and cause 461,000 deaths. The purpose of this study was to find out whether there is an effect of giving deep breathing techniques to changes in oxygen saturation and respiratory frequency in bronchial asthma patients at the Emergency Room at Embung Fatimah Hospital, Batam City in 2022. This study was a pure experimental study with a pre and post test control group design. . The sample size in this study was 16 respondents in the treatment group and 16 respondents in the control group. The sampling technique used purposive sampling. Based on statistical tests using the Wilcoxon alternative test, it was found in the treatment group p-Value = 0.000 <0.05, which means that there is an effect of increasing oxygen saturation values ​​and respiratory frequency by administering deep breathing techniques with an average increase in pretest and posttest oxygen saturation of 4.81 and an increase in pretest and posttest respiratory frequency of 6.38. Whereas in the control group p-Value = 0.000 <0.05, which means there is an effect of increasing oxygen saturation values ​​and breathing frequency without deep breathing techniques with an average pretest and posttest increase of 3.63 and an increase in pretest and posttest respiratory frequency of 5.